Metode Pembelajaran Jarak Jauh Pada Mata Kuliah Gitar Klasik Lampung Pepadun di Prodi Pendidikan Musik, Fakultas Keguruan Ilmu Pendidikan, Universitas Lampung - Erizal Barnawi; Afrizal Yudha Setiawan (Musikolastika: Jurnal Pertunjukan dan Pendidikan Musik, 2021)
The difficulties in learning the Lampung Pepadun Classical Guitar practice are caused by several factors, including; 1) the learning process is not guided directly by trainers who are experts in their fields; 2) many students of the Music Education study program are not yet able to read block notation in the form of songs; 3) some students do not have the skills to play guitar with the correct technique. The long-term goal in learning Lampung Pepadun Classical Guitar is that students are able to become agents of change in preserving the art of Lampung Pepadun Classical Guitar and become pioneers in developing and creating music, both contemporary music and creative music. The specific target to be achieved in this research is the creation of a new teaching pattern in the field of Lampung traditional music, namely learning by using several applications and distance learning methods in accordance with the concept of learning. Several online learning methods have been applied using various applications such as Youtube, MP3, and Sibelius. Online learning is learning that is carried out without face to face directly, using smartphone/gadget/laptop devices, and video conferencing platforms as a space for the learning process to take place. However, the seven learning components which include teachers/lecturers, students, objectives, materials, methods, media, and evaluation must remain an integral component of online learning, which will be integrated in achieving learning objectives